KAJIAN MENGENAI KEMAMPUAN MODAL SENDIRI DALAM MENJAMIN KESELURUHAN HUTANG PERUSAHAAN (Studi pada Perusahaan Bisi International Tbk Tahun 2017-2019) - Akhmad Akhmad; Labandingi Latoki (Jurnal Ekonomi Trend, 2021)
This study aims to analyze the ability of its own capital owned by Bisi International Tbk to guarantee all of its debts. So the approach used is a case study. Data collection is done by documentation method and the data taken is secondary data. The data comes from the 2017- 2019 financial statements. The analysis technique in this study uses financial ratios, namely comparing total debt with own capital. The results of research and studies reveal that the company's financial condition, especially the guarantee of capital on debt, tends to be in good condition. This can be seen from the amount of each rupiah of own capital that is able to cover every rupiah of costs. This research needs to be expanded by analyzing the relationship and the influence of other components that affect the improvement of the company's financial performance. Keywords: Current Debt, Long-Term Debt, Own Capital